Immature skulls of the theropod dinosaur Coelophysis bauri from Ghost Ranch, New Mexico - Jeb E. Bugos; Skye N. McDavid (Acta Palaeontologica Polonica)
The theropod dinosaur Coelophysis bauri is well known from the famous Rhaetian, Late Triassic mass death assemblage from the Coelophysis Quarry at Ghost Ranch, New Mexico. This research describes the skulls of two small individuals of C. bauri. Both skulls are mostly complete, though they are missing premaxillae, and most posterior skull bones are either missing or badly damaged. Both specimens preserve hyoids, making them excellent candidates for hyoid histology. These two skulls have different proportions from other Coelophysis skulls from Ghost Ranch, especially in the large size of the orbit, short and flat triangular teeth, and thinner bones. These differences are interpreted as representing ontogenetic variation, with these skulls representing skeletally immature, partially developed individuals.